Pertanggungjawaban Hukum terhadap Praktik Endorsement, Influencer dan Selebgram pada Platform Media Sosial di Indonesia - Alia Firhat (Jurnal Hukum Lex Generalis, 2026)
This research explores the legal accountability of influencers and selebgrams in the context of social media endorsements in Indonesia, employing a qualitative empirical legal methodology. The study is grounded in the growing prominence of influencers as digital marketing agents, whose legal standing remains ambiguously defined within Indonesia’s current regulatory landscape. The empirical legal inquiry was carried out through in-depth interviews with managers, influencers and selebgrams actively engaged in endorsement practices. The findings reveal the unclear legal status of influencers, the dominant role of managers in organizing endorsement collaborations and the gap between legal regulations and actual endorsement practices. The study concludes that a proportional legal responsibility framework is necessary.